Sistem Pendukung Keputusan Penentuan Kinerja Sales Terbaik Menggunakan Kombinasi Grey Relational Analysis dan Pembobotan Rank Sum - Citra, Puspa; Sriyasa, I Wayan; Santoso, Heri Bambang (Jurnal Ilmiah Computer Science, 2024)
The best sales performance is one of the key elements in the business world that not only reflects the ability of individuals or sales teams to achieve sales targets, but also becomes a key pillar in the growth and success of the company. The problem in choosing the best sales performance is that there is no decision support system model in choosing the best sales performance. The purpose of this study is to determine the best sales performance by applying the GRA method and rank sum weighting in the assessment of existing sales performance, so that the results of the sales performance appraisal will be a recommendation for companies in determining the best sales performance. The ranking results showed the highest value of 0.1309 obtained by sales Hadi for rank 1, the next highest value of 0.0941 obtained by sales Arini for rank 2, the next highest value of 0.0777 obtained by sales Cindy for rank 3.